Comparing Pooled Peptides with Intact Protein for Accessing Cross-presentation Pathways for Protective CD8+ and CD4+ T Cells - Zhang, H; Hong, H; Li, D; Ma, S; Di, Y; Stoten, A; Haig, N; Di Gleria, K; Yu, Z; Xu, X; McMichael, A; Jiang, S (American Society for Biochemistry & Molecular Biology, 2009)
To better understand the mechanisms of intracellular trafficking and presentation of exogenous peptides by antigen-presenting cells (APC), we compared the handling of overlapping 24-mer peptides from HIV Nef either mixed or covalently linked in tandem in one protein. Once internalized, peptides trafficked not only to endosomes but also to cytosol, and activated CD8(+) and CD4(+) T cells. In contrast, whole protein was found to traffic only to the endosomal compartments, and primarily activated CD4(+) T cells. Finally, with adjuvant, overlapping peptides were capable of protecting against lethal viral challenge, whereas the intact protein was less protective. These data suggest that overlapping long peptides are cross-presented through more varied intracellular routes and are more efficient in priming protective immunity than the whole protein.